Kepatuhan Wajib Pajak Di Kantor Pelayanan Pajak Pratama Denpasar Barat Dengan Sanksi Pajak Sebagai Variabel Moderasi - Yuesti, Anik; Prananta, Nyoman Gede Wimana; Bhegawati, Desak Ayu Sriary (Universitas 17 Agustus 1945 Jakarta, 2022)
Tax is a mandatory contribution owed to the State by an individual or a coercive entity based on the law which does not receive direct compensation. Tax compliance is the most important thing for all countries, both developed and developing countries. This study aims to examine the effect of service quality, taxpayer awareness, tax socialization, and tax rates on taxpayer compliance at the West Denpasar Pratama Tax Office with tax sanctions as a moderating variable.The method of determining the sample in this study is the accidental sampling method and uses the Slovin formula to get the number of 100 people. The analytical tool used Moderated Regression Analysis.The results showed that service quality, taxpayer awareness, tax socialization, and tax rates had a positive effect on individual taxpayer compliance. Tax sanctions are able to moderate the effect of service quality, taxpayer awareness, tax socialization, and tax rates on individual taxpayer compliance.